Analisa dan Perancangan Sistem Informasi Pendukung Keputusan Berbasis Web Untuk Pemilihan Penghuni Asrama UNAI Menggunakan Metode SAW - Yulianus Palopak; Zefanya Lumbantobing (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2019)
The purpose of this study is to design a computer-based system that can be used to assist in the decision making process. The need for a decision support system in terms of determining students for the special dormitory intended for students who are financially incapable who are studying at the Adventist University of Indonesia (UNAI). Usually the decision-making process often involves many criteria, then a method that can support decision making involving multi criteria or Multi Criteria Decision Making (MCDM) is used. Simple Additive Weighting (SAW) is a method that commonly used in supporting multi-criteria decision making. The model in SAW is used to determine the rank of alternatives that are displayed in the form of web-based computer applications so as to facilitate users of both students and UNAI management. The results of this study is a web-based computer-based decision support system that can help to determine decision-making on the selection of Special Dormitory registration at UNAI. Furthermore, this research can be developed using other methods for more effective decision making and can also be displayed on other platforms such as mobile applications. Keywords: Decision Support System, Simple Additive Weighting (SAW) Method, Multi Criteria Decision Making (MCDM), Information System